Olefin cross metathesis based de novo synthesis of a partially protected L-amicetose and a fully protected L-cinerulose derivative - Schmidt, Bernd; Hauke, Sylvia (Beilstein Journal of Organic Chemistry, 2014)
Cross metathesis of a lactate derived allylic alcohol and acrolein is the entry point to a de novo synthesis of 4-benzoate protected L-amicetose and a cinerulose derivative protected at C5 and C1.
Keywords: carbohydrates; de novo synthesis; lactate; metathesis; ruthenium

(untitled) - La Ferla, B.; Airoldi, C.; Zona, C.; Orsato, A.; Cardona, F.; Merlo, S.; Sironi, E.; D'Orazio, G.; Nicotra, F. (Nat. Prod. Rep., 2011)

Biochemie der Antibiotika - Gräfe, U. (Spektrum Verlag, 1992)

(untitled) - Hoffmeister, D.; Dräger, G.; Ichinose, K.; Rohr, J.; Bechthold, A. (J. Am. Chem. Soc., 2003)

(untitled) - Hoffmeister, D.; Weber, M.; Dräger, G.; Ichinose, K.; Dürr, C.; Bechthold, A. (ChemBioChem, 2004)

(untitled) - Pérez, M.; Lombó, F.; Zhu, L.; Gibson, M.; Braña, A. F.; Rohr, J.; Salas, J. A.; Méndez, C. (Chem. Commun., 2005)

(untitled) - Kirschning, A.; Bechthold, A. F.-W.; Rohr, J. (Top. Curr. Chem., 1997)

(untitled) - Kunimoto, S.; Someno, T.; Yamazaki, Y.; Lu, J.; Esumi, H.; Naganawa, H. (J. Antibiot., 2003)

(untitled) - Someno, T.; Kunimoto, S.; Nakamura, H.; Naganawa, H.; Ikeda, D. (J. Antibiot., 2005)

(untitled) - Lu, J.; Kunimoto, S.; Yamazaki, Y.; Kaminishi, M.; Esumi, H. (Cancer Sci., 2004)

(untitled) - Arcamone, F.; Cassinelli, G. (Curr. Med. Chem., 1998)

(untitled) - Oki, T.; Matsuzawa, Y.; Yoshimoto, A.; Numata, K.; Kitamura, I.; Hori, S.; Takamatsu, A.; Umezawa, H.; Ishizuka, M.; Naganawa, H.; Suda, H.; Hamada, M.; et al. (J. Antibiot., 1975)

(untitled) - Komiyama, T.; Oki, T.; Inui, T.; Takeuchi, T.; Umezawa, H. (Gann, 1979)

(untitled) - Lee, Y.-L.; Chen, C.-W.; Liu, F.-H.; Huang, Y.-W.; Huang, H.-M. (PLoS One, 2013)

(untitled) - Kirschning, A.; Jesberger, M.; Schöning, K.-U. (Synthesis, 2001)

(untitled) - Thiem, J.; Klaffke, W. (Top. Curr. Chem., 1990)

(untitled) - Seeberger, P. H.; Danishefsky, S. J. (Acc. Chem. Res., 1998)

(untitled) - Seeberger, P. H.; Haase, W.-C. (Chem. Rev., 2000)

(untitled) - Lajšić, S.; Miljković, D.; Ćetković, G. (Carbohydr. Res., 1992)

(untitled) - Bethell, G. S.; Ferrier, R. J. (J. Chem. Soc., Perkin Trans. 1, 1973)

(untitled) - Pedersen, C.; Jensen, H. S. (Acta Chem. Scand., 1994)

(untitled) - Spohr, U.; Paszkiewicz-Hnatiw, E.; Morishima, N.; Lemieux, R. U. (Can. J. Chem., 1992)

(untitled) - Kjølberg, O.; Neumann, K. (Acta Chem. Scand., 1992)

(untitled) - Wang, H.-Y. L.; Wu, B.; Zhang, Q.; Kang, S.-W.; Rojanasakul, Y.; O'Doherty, G. A. (ACS Med. Chem. Lett., 2011)

(untitled) - Wang, H.-Y. L.; Xin, W.; Zhou, M.; Stueckle, T. A.; Rojanasakul, Y.; O'Doherty, G. A. (ACS Med. Chem. Lett., 2011)

(untitled) - Zhu, L.; Talukdar, A.; Zhang, G.; Kedenburg, J. P.; Wang, P. G. (Synlett, 2005)

(untitled) - Kirschning, A.; Hary, U.; Ries, M. (Tetrahedron, 1995)

(untitled) - Noecker, L. A.; Martino, J. A.; Foley, P. J.; Rush, D. M.; Giuliano, R. M.; Villani, F. J., Jr (Tetrahedron: Asymmetry, 1998)

(untitled) - Berti, G.; Caroti, P.; Catelani, G.; Monti, L. (Carbohydr. Res., 1983)

(untitled) - Marco, J. L. (Synth. Commun., 1989)

(untitled) - Itoh, T.; Yoshinaka, A.; Sato, T.; Fujisawa, T. (Chem. Lett., 1985)

(untitled) - Fuganti, C.; Grasselli, P. (J. Chem. Soc., Chem. Commun., 1978)

(untitled) - Aidhen, I. S.; Satyamurthi, N. (Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem., 2008)

(untitled) - McDonald, F. E.; Zhu, H. Y. H. (J. Am. Chem. Soc., 1998)

(untitled) - Zhu, L.; Kedenburg, J. P.; Xian, M.; Wang, P. G. (Tetrahedron Lett., 2005)

(untitled) - Schmidt, B.; Hauke, S. (Org. Biomol. Chem., 2013)

(untitled) - Schmidt, B.; Biernat, A. (Chem.–Eur. J., 2008)

(untitled) - Ley, S. V.; Armstrong, A.; Díez-Martín, D.; Ford, M. J.; Grice, P.; Knight, J. G.; Kolb, H. C.; Madin, A.; Marby, C. A.; Mukherjee, S.; Shaw, A. N.; Slawin, A. M. Z.; et al. (J. Chem. Soc., Perkin Trans. 1, 1991)

(untitled) - Chatterjee, A. K.; Morgan, J. P.; Scholl, M.; Grubbs, R. H. (J. Am. Chem. Soc., 2000)

(untitled) - Cossy, J.; BouzBouz, S.; Hoveyda, A. H. (J. Organomet. Chem., 2001)

(untitled) - Dinh, M.-T.; BouzBouz, S.; Peglion, J.-L.; Cossy, J. (Synlett, 2005)

(untitled) - Chandra Rao, D.; Kumar Reddy, D.; Shekhar, V.; Venkateswarlu, Y. (Tetrahedron Lett., 2013)

(untitled) - Miao, X.; Fischmeister, C.; Bruneau, C.; Dixneuf, P. H. (ChemSusChem, 2009)

(untitled) - Mohapatra, D. K.; Maity, S.; Rao, T. S.; Yadav, J. S.; Sridhar, B. (Eur. J. Org. Chem., 2013)

(untitled) - Paul, T.; Andrade, R. B. (Tetrahedron Lett., 2007)

(untitled) - Achmatowicz, O.; Szechner, B. B. (Bull. Acad. Pol. Sci., Ser. Sci. Chim., 1971)

(untitled) - Scholl, M.; Ding, S.; Lee, C. W.; Grubbs, R. H. (Org. Lett., 1999)

(untitled) - Garber, S. B.; Kingsbury, J. S.; Gray, B. L.; Hoveyda, A. H. (J. Am. Chem. Soc., 2000)

(untitled) - Gessler, S.; Randl, S.; Blechert, S. (Tetrahedron Lett., 2000)

WO Pantent Applcation - Arlt, D.; Bieniek, M.; Karch, R. (Novel Metathesis Catalysts, 2008)

(untitled) - Mutlu, H.; Montero de Espinosa, L.; Türünç, O.; Meier, M. A. R. (Beilstein J. Org. Chem., 2010)

(untitled) - Schmidt, B. (Eur. J. Org. Chem., 2004)

(untitled) - Schmidt, B. (J. Mol. Catal. A, 2006)

(untitled) - Higman, C. S.; Plais, L.; Fogg, D. E. (ChemCatChem, 2013)

(untitled) - Forman, G. S.; McConnell, A. E.; Tooze, R. P.; van Rensburg, W. J.; Meyer, W. H.; Kirk, M. M.; Dwyer, C. L.; Serfontein, D. W. (Organometallics, 2005)

(untitled) - Forman, G. S.; Tooze, R. P. (J. Organomet. Chem., 2005)

(untitled) - Samojłowicz, C.; Bieniek, M.; Grela, K. (Chem. Rev., 2009)

(untitled) - Connon, S. J.; Blechert, S. (Angew. Chem., Int. Ed., 2003)

(untitled) - Connon, S. J.; Blechert, S. (Top. Organomet. Chem., 2004)

(untitled) - Schmidt, B.; Kunz, O.; Petersen, M. H. (J. Org. Chem., 2012)

(untitled) - Schmidt, B.; Kunz, O. (Beilstein J. Org. Chem., 2013)

(untitled) - Neises, B.; Steglich, W. (Angew. Chem., Int. Ed. Engl., 1978)

(untitled) - Baker, B. A.; Bošković, Z. V.; Lipshutz, B. H. (Org. Lett., 2008)

(untitled) - Mahoney, W. S.; Brestensky, D. M.; Stryker, J. M. (J. Am. Chem. Soc., 1988)

(untitled) - Young, J. G.; Hartung, W. H.; Daniels, H. H. (J. Org. Chem., 1953)

(untitled) - Haukaas, M. H.; O'Doherty, G. A. (Org. Lett., 2002)

(untitled) - Kim, S.; Jacobo, S. M.; Chang, C.-T.; Bellone, S.; Powell, W. S.; Rokach, J. (Tetrahedron Lett., 2004)

(untitled) - Felpin, F.-X.; Fouquet, E. (Chem.–Eur. J., 2010)

(untitled) - Schmidt, B.; Kunz, O.; Biernat, A. (J. Org. Chem., 2010)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2008)

(untitled) - Gorla, F.; Venanzi, L. M. (Helv. Chim. Acta, 1990)

(untitled) - Seki, M. (Synthesis, 2006)

(untitled) - Felpin, F.-X.; Ayad, T.; Mitra, S. (Eur. J. Org. Chem., 2006)